2015
DOI: 10.1016/j.msec.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced by UV radiation in the presence of sodium benzoate in films formulated with polyvinyl alcohol and carboxymethyl cellulose

Abstract: This work was focused on: i) developing single and blend films based on carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVOH) studying their properties, ii) analyzing the interactions between CMC and PVOH and their modifications UV-induced in the presence of sodium benzoate (SB), and iii) evaluating the antimicrobial capacity of blend films containing SB with and without UV treatment. Once the blend films with SB were exposed to UV radiation, they exhibited lower moisture content as well as a greater elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…This finding was similar to the results of Lizundia et al ., who reported a continuous increase of TS at the expense of ductility upon nanohybrids loading. It was found that the EAB depended on the interactions between the matrixes and the active components . Further, the excess amount of MMCSC affected the crystalline structure and microstructure of the films and led to a reduction of EAB …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to the results of Lizundia et al ., who reported a continuous increase of TS at the expense of ductility upon nanohybrids loading. It was found that the EAB depended on the interactions between the matrixes and the active components . Further, the excess amount of MMCSC affected the crystalline structure and microstructure of the films and led to a reduction of EAB …”
Section: Resultsmentioning
confidence: 99%
“…(a), FTIR spectra confirmed that the molecular chain structure of MCSC and cellulose segments held the same peaks when it was treated by ultrasonics and microwaves before and after. As with the research of Villarruel et al ., it was difficult to direct cleavage functional groups to form free radicals at lower energy levels …”
Section: Resultsmentioning
confidence: 99%
“…Tensile test was an important evaluation of film properties, tensile strength was represented the maximum resistance until it was break. Using dynamic‐mechanical thermal equipment Q800 (USA) to test the mechanical properties of polyvinyl alcohol films and CMC films had been reported, and indicated that CMC films had the characteristics of stiff and brittle, while polyvinyl alcohol films had better flexibility (Villarruel and others ). As shown in Figure (A) and Table , TS and EAB of the CDP, CDP/CSC and CDP/NCSC films were presented.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the EAB value of CDP, CDP/CSC, and CDP/NCSC films was 60.067%, 82.75%, and 65.9166%, respectively. It was found that the EAB might be depended on the interactions generated between the polymers and the active component (Villarruel and others ). The EAB value of CDP/NCSC was lower than CDP/CSC, it was due to the nanofiller prevents motion of polymer matrix (Atef and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Han and Floros (1997) found that potassium sorbate (1% w/w) incorporated in LDPE films not only extended the lag time of a bakery yeast but also reduced the growth rate and its maximum growth. Villarruel et al (2015) In general, potassium sorbate and sodium benzoate significantly inhibited the growth of spoilage flora in minimally processed fruit. As observed for the volatile antimicrobials, the application of potassium sorbate and/or sodium benzoate by dipping or as a coating were more often reported than active packaging applications.…”
Section: Sodium Benzoatementioning
confidence: 97%